Should we review our prophylaxis approach for increased antibiotic resistance in transrectal prostate biopsy? - Adalet Altunsoy; Şeref Coşer; Nizamettin Kemirtlek; Ibrahim Can Aykanat; Melih Balci; Hürrem Bodur; Altuğ Tuncel (Journal of Infection in Developing Countries)
Introduction: This study aims to show the bacteriologic picture of acute prostatitis and bacteremia caused by infective agent after transrectal ultrasound-guided prostate biopsy (TRUSBx) and to determine the resistance rates of the infections in patients undergoing transrectal biopsy and to guide prophylaxis approach before biopsy.